2011 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2011
DOI: 10.1109/ceidp.2011.6232737
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into improving the breakdown strength and thermal conduction of an epoxy system using boron nitride

Abstract: It has been seen previously that addition of fillers to host material systems can create composites with superior properties. In particular polymers have been shown to be good hosts for such property-boosting fillers. This investigation looks at such a polymer based nanocomposite, with the aim to produce a thermally conductive high voltage insulator. A standard thermosetting epoxy system and hardener were chosen to act as the host polymer due to its good initial mechanical and electrical properties. This syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…It has also been shown in the literature that dielectric breakdown strength could be slightly improved with nanometric filler sizes [9] whereas incorporation of submicrometric and micrometric particles in epoxy resin resulted in similar breakdown strengths compared to the neat epoxy at BN loadings of 10 wt% [7,9].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It has also been shown in the literature that dielectric breakdown strength could be slightly improved with nanometric filler sizes [9] whereas incorporation of submicrometric and micrometric particles in epoxy resin resulted in similar breakdown strengths compared to the neat epoxy at BN loadings of 10 wt% [7,9].…”
Section: Introductionmentioning
confidence: 77%
“…Recent studies have shown an improved thermal conductivity of composites after incorporating BN in an epoxy matrix [3][4][5][6], with a trend of superior performances by reducing filler sizes in non percolating networks [4,7]. Partially very high BN particle loadings of 20 wt% [4] and up to 90 wt% [5,6,8] in epoxy resins have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a new material with improved dielectric and thermal properties may be produced by combining polystyrene and h-BN. The structure of h-BN is analogous to graphite, where there is an equal number of boron and nitrogen atoms firmly bound together forming platelets stacked on top of each other [3]. Efforts have been made by researchers to exfoliate h-BN using chemical and mechanical methods to overcome the Van der Waals forces between the stacked layers, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has uses in electronics and is an ideal model matrix for this type of research. BN has been chosen as a nanofiller in this study due to its attractive electrical, thermal, and mechanical properties, such as high breakdown strength and thermal conductivity [3]. Thus a new material with improved dielectric and thermal properties may be produced by combining polystyrene and h-BN.…”
Section: Introductionmentioning
confidence: 99%
“…Since the operation efficiency of these systems is directly related to the performance of their epoxy insulations [1], several attempts have been made to vary the properties of these thermosetting materials to suit particular application. For example, the addition of nano-and microsized fillers which improved the thermal properties of epoxy resin in [2] and changing the architecture structure of the epoxy using reactive modifiers which enhanced the mechanical strength of the epoxy matrix used in [3]. As part of a study of modified epoxy resin systems, the network structure was varied using octyl/decyl glycidyl ether [4].…”
Section: Introductionmentioning
confidence: 99%